2020
DOI: 10.47104/ebnrojs3.v2i4.156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simulation-Based Educational Program on Maternity Nurses' Performance regarding Obstetrical Emergencies during Pregnancy

Abstract: Context: Simulation-based nursing education is an increasingly and wide-spread preferred educational approach. It offers opportunities to acquire clinical skills and decision-making through various situational experiences. Aim: The research aimed to investigate the effect of simulation-based educational program on maternity nurses' performance regarding obstetrical emergencies during pregnancy. Methods: A quasi-experimental research (one group pre/post-test) design was adopted to fulfill the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Also, these findings are consistent with Farahat et al, (2018), who studied "the effect of Clinical Audit on the quality of postoperative nursing care provided to women undergoing CS at Woman's Health Hospital" in Egypt and reported that there was a significant improvement in nurses' practices related to monitoring vital signs, palpating fundus and surgical site care after implementing educational strategy. In accordance with El-Sharkawy et al, (2020) 2019) who showed a strong positive correlation between knowledge and practice scores were generated. Regarding satisfaction of women having CS with health care provider interaction, on posttest women showed higher level of satisfaction than on pretest.…”
Section: Discussionsupporting
confidence: 64%
“…Also, these findings are consistent with Farahat et al, (2018), who studied "the effect of Clinical Audit on the quality of postoperative nursing care provided to women undergoing CS at Woman's Health Hospital" in Egypt and reported that there was a significant improvement in nurses' practices related to monitoring vital signs, palpating fundus and surgical site care after implementing educational strategy. In accordance with El-Sharkawy et al, (2020) 2019) who showed a strong positive correlation between knowledge and practice scores were generated. Regarding satisfaction of women having CS with health care provider interaction, on posttest women showed higher level of satisfaction than on pretest.…”
Section: Discussionsupporting
confidence: 64%